Congenital pulmonary airway malformation and sequestration: Two standpoints for a single condition - Fievet, Lucile; Natale, Claudia; D′Journo, Xavier-Benoit; Coze, Stéphanie; Dubus, Jean-Christophe; Guys, Jean-Michel; Thomas, Pascal; De Lagausie, Pascal (Journal of minimal access surgery, 2015)
In adults, congenital pulmonary malformations are candidates for surgery due to symptoms. A pre-natal diagnosis is simple and effective, and allows an early thoracoscopic surgical treatment. A retrospective study was performed to assess management in two different populations of adults and children to define the best strategy. Pulmonary malformations followed at the University Hospital from 2000 to 2012 were reviewed. Clinical history, malformation site, duration of hospitalisation, complications and pathology examinations were collected. A total of 52 cases (33 children, 19 adults) were identified. In children, 28 asymptomatic cases were diagnosed pre-natally and 5 during the neonatal period due to infections. Surgery was performed on the children between the ages of 2 and 6 months. Nineteen adults underwent surgery, 16 because of symptoms and 3 adults for anomalies mimicking tumours. The mean age within the adult group was 42.5 years. In children, there was one thoracotomy and 32 thoracoscopies, with 7 conversions for difficult exposure, dissection of vascular pedicles, bleeding or bronchial injury. In the adults, there were 15 thoracotomies and 4 thoracoscopies, with one conversion. Post-operative complications in the adults were twice as frequent than in children. The mean time of the children's hospitalisation was 7.75 days versus 7.16 days for the adults. Pathological examinations showed in the children: 7 sequestrations, 18 congenital cystic pulmonary malformations (CPAM), 8 CPAM associated sequestrations; in adults: 16 sequestrations, 3 intra-pulmonary cysts. Early thoracoscopic surgery allows pulmonary parenchyma conservation with pulmonary development, reduces respiratory and infectious complications, eliminates a false positive cancer diagnosis later in life and decreases risks of thoracic parietal deformation.